Novel Bullet for Dyslipidemia and Cardiovascular Disease in the Horizon: Does Genetics Contribute to the Blueprint? - Anwar Santoso (Jurnal Kardiologi Indonesia, 2014)
The development of novel therapy for dyslipidemia and cardiovascular diseases (CVD) had been constrained by some challenges, and several recent approaches have failed for lack of efficacy. Progress had been made by a single, greatest contribution from statins in reducing the risk of CVD. However, the burden of CVD and residual risk remains quite high, and new pathways to prevent and treat the diseases are still needed. Despite this clear unmet need, nevertheless many research institutions have begun to withdraw their efforts in discovering ‘the new bullet’ for this prevalent diseases1.